Genetic basis of rotator cuff injury: a systematic review - Umile Giuseppe Longo; Vincenzo Candela; Alessandra Berton; Giuseppe Salvatore; Andrea Guarnieri; Joseph DeAngelis; Ara Nazarian; Vincenzo Denaro (BMC, 2019)
Abstract Background Rotator cuff disease is a widespread musculoskeletal pathology and a major cause of shoulder pain. Studies on familial predisposition suggest that genetic plays a role in the pathogenesis of rotator cuff disease. Several genes are responsible for rotator cuff disease. The aim of this study was to perform a systematic review on genetic association between rotator cuff disease and genes variations. Methods A systematic review of the literature was performed, in accordance with the PRISMA guidelines. PubMed, Medline, CINAHL, Cochrane, Embase and Google Scholar databases were searched comprehensively using the keywords: "Rotator cuff", "Gene", "Genetic", "Predisposition", "Single-nucleotide polymorphism" and "Genome-wide association". Results 8 studies investigating genes variations associated with rotator cuff tears were included in this review. 6 studies were case-control studies on candidate genes and 2 studies were GWASs. A significant association between SNPs and rotator cuff disease was found for DEFB1, FGFR1, FGFR3, ESRRB, FGF10, MMP-1, TNC, FCRL3, SASH1, SAP30BP, rs71404070 located next to cadherin8. Contradictory results were reported for MMP-3. Conclusion Further investigations are warranted to identify complete genetic profiles of rotator cuff disease and to clarify the complex interaction between genes, encoded proteins and environment. This may lead to individualized strategies for prevention and treatment of rotator cuff disease. Level of evidence Level IV, Systematic Review.